Fathers and Gender: Key Factors Shaping the Resilience of Children After the Cianjur Earthquake - Famila, Shanina Rosa; Latifah, Melly; Simanjuntak, Megawati (Journal of Family Sciences, 2024)
The November 2022 earthquake in Cianjur had both adverse and beneficial psychological effects, with children being among the most susceptible groups. This aims the factors influencing the resilience of child disaster survivors, focusing on paternal factors such as educational background, income, and the children's gender. The study employed a quantitative approach with an explanatory research design. Participants were 196 students from grades 4 to 6 residing in Cijedil Village, Cugenang District, Cianjur Regency. The sampling technique used in this research is purposive sampling, and Spearman's correlation was applied to analyze the results. The findings revealed a significant positive relationship between fathers' education and income and the resilience of child earthquake survivors in Cianjur, with the father's education emerging as the most influential factor. While girls demonstrated a higher average resilience score compared to boys, the difference was not statistically significant. This research contributes to understanding children's resilience after disasters and offers insights to strengthen children's resilience against the psychological impact of such events. The research proposes practical recommendations for improving child resilience in disaster-prone areas like Cianjur, focusing on strengthening economic support for families, promoting parental education, enhancing access to education and mental health services, and developing community-based resilience programs.